Whole-genome sequence of Starmerella bacillaris PAS13, a nonconventional enological yeast with antifungal activity - Treu, Laura; Duarte, Vinícius da Silva; Carlot, Milena; Nadai, Chiara; Campanaro, Stefano; Giacomini, Alessio; Corich, Viviana; Lemos Junior, Wilson José Fernandes (Genome Announcements, 2017)
Starmerella bacillaris is a fermentative yeast commonly found in vineyards. Here, we present the draft genome sequence of S. bacillaris PAS13, a nonconventional enological yeast with a potential role as a biocontrol agent. This gene sequence will provide insights into the genetic basis of yeast activity against gray mold disease (Botrytis cinerea).
Keywords: Starmerella bacillaris; Nonconventional enological; Antifungal activity